Unpacking the factors that contribute to successful engagement of stakeholders in a volunteer camphost programme. Issue 2 (2nd April 2020) - Weiler, Betty; Caldicott, Rod
ABSTRACT: This case study aims to explore the factors that underpinned successful engagement of stakeholders in the development, piloting and evaluation of a volunteer camphost programme. The study is informed by both stakeholder theory and the volunteer management literature. Multiple data sources and mixed methods were used to uncover the perceptions of three key stakeholder groups: national park employees, volunteer camphosts, and park visitors. Informed by six factors of successful stakeholder engagement derived from a comprehensive review of the literature, the analysis confirmed the importance of stakeholders being (1) willing and able to participate, (2) tolerant of sharing power, and (3) open to change in how visitor services are delivered. The study also confirmed that the process of stakeholder engagement needs to (4) foster a shared vision and purpose for the camphost programme and (5) emphasise effective and on-going communication. A sixth factor, interdependency among stakeholders, appears to be of importance to the extent that the programme is mutually beneficial for park managers and volunteer camphosts. The findings also point to the need for early identification and sustained engagement of key stakeholders for successful development and implementation of volunteer programmes in national parks.